FINANCIAL MANAGEMENT IN IMPROVING TEACHER PERFORMANCE - Siregar, Linda Erawati (PT Rahis Cendekia Indonesia, 2023)
The birth of Law No. 22 of 1999 concerning regional autonomy affects the management of education in Indonesia. On the one hand, autonomy is an opportunity for educational units to manage their own schools both in terms of curriculum development and funding aspects, but on the other hand it becomes a threat when schools do not have readiness both in terms of human resources (HR) and funding, therefore the competence of school principals in School financial management is absolutely necessary so that both teachers and employees can provide quality education.